Cutaneous Granulomas and Ataxia-Telangiectasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Development of cutaneous granulomas in 8 patients with ataxia-telangiectasia is reported from the Departments of Pediatrics and Dermatology, Northwestern University Medical School, Chicago, IL; the Hospital for Sick Children, Toronto, Canada; Henry Ford Hospital, Detroit, MI; and University of North Carolina, Chapel Hill.